The Ties that Bind: Public Opinion and Linked Fate among Women of Color. (2nd January 2023) - Carey, Tony E.; Lizotte, Mary-Kate
ABSTRACT: Although women of color share the same gender identity, their differing racial identities lead to questions about whether they might mobilize collectively over a shared political agenda. Using the 2020 Collaborative Multiracial Post-Election Survey, we examine how linked fate among women of color shapes the political attitudes and policy preferences of Black women, Latinas, and Asian American/Pacific Islander women. Our expectation is that linked fate toward women of color will shape perception and preferences in three particular issue areas: policies that are intended to reduce racial inequity (e.g., police reform), perceptions of gender discrimination, and social welfare policies aimed at aiding lower income individuals. Our results strongly confirm these expectations indicating immense potential for cross-racial coalitions among women of color across issue areas.